Using the Multiple Intelligences as a learning intervention: a model for coaching and mentoring - Colleen Harding (International Journal of Evidence Based Coaching and Mentoring, 2006)
The purpose of this study was to explore the ways in which Gardner’s Multiple Intelligences (MI) could be incorporated into a model for coaching and mentoring. The research was conducted through a qualitative study using Action Research. Six coach-mentors worked with six learners and devised interventions to emphasise the MI through the coaching-mentoring process in a variety of contexts. Both the impact on the progress of the learners and the impact on the practice of the coach-mentors were analysed. The study concluded by acknowledging that in emphasising a range of MI during the coaching-mentoring process learners were stimulated to progress their learning. The discipline of aiming to use all of the MI encouraged the coach-mentors to take risks in designing experiential interventions. The creation of a MI Model and a MI Toolbox for Coaching and Mentoring gave coach-mentors a structure in which to work and a language for discussing and developing their work. The Model and Toolbox exist as tangible outcomes of the study.